Clinical benefit and cost of breakthrough cancer drugs approved by the US Food and Drug Administration. Issue 19 (22nd July 2020) - Molto, Consolación; Hwang, Thomas J.; Borrell, Maria; Andres, Marta; Gich, Ignasi; Barnadas, Agustí; Amir, Eitan; Kesselheim, Aaron S.; Tibau, Ariadna
Abstract : Background: The clinical benefit and pricing of breakthrough‐designated cancer drugs are uncertain. This study compares the magnitude of the clinical benefit and monthly price of new and supplemental breakthrough‐designated and non–breakthrough‐designated cancer drug approvals. Methods: A cross‐sectional cohort comprised approvals of cancer drugs for solid tumors from July 2012 to December 2017. For each indication, the clinical benefit from the pivotal trials was scored via validated frameworks: the American Society of Clinical Oncology Value Framework (ASCO‐VF), the American Society of Clinical Oncology Cancer Research Committee (ASCO‐CRC), the European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO‐MCBS), and the National Comprehensive Cancer Network (NCCN) Evidence Blocks. A high clinical benefit was defined as scores ≥ 45 for the ASCO‐VF, overall survival gains ≥ 2.5 months or progression‐free survival gains ≥ 3 months for all cancer types for the ASCO‐CRC criteria, a grade of A or B for trials of curative intent and a grade of 4 or 5 for trials of noncurative intent for the ESMO‐MCBS, and scores of 4 and 5 and a combined score ≥ 16 for the NCCN Evidence Blocks. Monthly Medicare drug prices were calculated with Medicare prices and DrugAbacus. Results: This study identified 106 trials supporting approval of 52 drugs for 96 indications. Forty percent of these indications received the breakthrough designation. Among the included trials, 33 (43%), 46 (73%), 35 (34%), and 67 (69%) met the thresholds established by the ASCO‐VF, ASCO‐CRC, ESMO‐MCBS, and NCCN, respectively. In the metastatic setting, there were higher odds of clinically meaningful grades in trials supporting breakthrough drugs with the ASCO‐VF (odds ratio [OR], 3.69; P  = .022) and the NCCN Evidence Blocks (OR, 5.80; P  = .003) but not with the ASCO‐CRC (OR, 3.54; P  = .11) or version 1.1 (v1.1) of the ESMO‐MCBS (OR, 1.22; P  = .70). The median costs of breakthrough therapy drugs were significantly higher than those of nonbreakthrough therapies ( P  = .001). Conclusions: In advanced solid cancers, drugs that received the breakthrough therapy designation were more likely than nonbreakthrough therapy drugs to be scored as providing a high clinical benefit with the ASCO‐VF and the NCCN Evidence Blocks but not with the ESMO‐MCBS v1.1 or the ASCO‐CRC scale. Abstract : In advanced solid cancers, drugs approved under the breakthrough therapy designation have higher odds for a high clinical benefit according to version 2 of the American Society of Clinical Oncology (ASCO) Value Framework and the National Comprehensive Cancer Network Evidence Blocks. Similar proportions of approved breakthrough and nonbreakthrough therapy drugs meet the thresholds for high benefit with version 1.1 of the European Society for Medical Oncology Magnitude of Clinical Benefit Scale and the ASCO Cancer Research Committee scale.